Differential expression of immune-related cytokine genes in response to J group avian leukosis virus infection in vivo. Issue 1 (March 2015) - Gao, Yanni; Liu, Yongzhen; Guan, Xiaolu; Li, Xiaofei; Yun, Bingling; Qi, Xiaole; Wang, Yongqiang; Gao, Honglei; Cui, Hongyu; Liu, Changjun; Zhang, Yanping; Wang, Xiaomei; et al.
Highlights We test cytokine expressions in different organs of ALV-J infected chickens. The expressions of IL-18, IFN-α and IFN-γ all up-regulated after ALV-J infection. Spleen is the most important organ fighting against ALV-J with cytokines. Cytokines were expressed early in avian leukosis virus infection.